2021
DOI: 10.1007/s11764-021-01006-w
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer follow-up costs in Germany from 2000 to 2015

Abstract: Purpose The main objective of this study is to estimate and evaluate 10-year follow-up costs after prostate cancer treatment with curative (surgery, radiotherapy) and non-curative intent (hormone, androgen deprivation) per patient in Germany in 2000, 2008, and 2015. Methods Prostate cancer follow-up recommendations were extracted from the European Association of Urology guidelines from 2000 to 2015. Per patient costs were calculated with a detailed micro-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Prostate cancer survivors under hormone treatment require a more intensive follow-up, when compared with breast or colorectal cancer survivors. A German study reported that the estimated 10-year follow-up costs for prostate cancer survivors has increased, in particular if hormone therapy is prescribed, from EUR 1361 in 2000 to EUR1777 in 2015, after accounting for inflation (Michaeli and Michaeli 2021 ). In addition, a greater portion of these increased costs were borne by survivors rather than insurance providers.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer survivors under hormone treatment require a more intensive follow-up, when compared with breast or colorectal cancer survivors. A German study reported that the estimated 10-year follow-up costs for prostate cancer survivors has increased, in particular if hormone therapy is prescribed, from EUR 1361 in 2000 to EUR1777 in 2015, after accounting for inflation (Michaeli and Michaeli 2021 ). In addition, a greater portion of these increased costs were borne by survivors rather than insurance providers.…”
Section: Discussionmentioning
confidence: 99%
“…An established costing methodology was employed to calculate the socio‐economic burden of RCC survivorship in Germany (Michaeli et al, 2021, 2022; Michaeli & Michaeli, 2022). In accordance with the EAU guidelines' risk‐stratification, we estimated costs across three distinct patient groups: low‐, medium‐, and high‐risk RCC.…”
Section: Methodsmentioning
confidence: 99%
“…The German Federal Joint Committee declines the financial coverage of such testing by health insurance funds. Available validated instruments should accompany the baseline prostate-specific antigen to optimize detection of clinically significant prostate cancer [4].…”
Section: Methodsmentioning
confidence: 99%